Penerapan Metode Bernyanyi Religi Dalam Meningkatkan Pengetahuan Keagamaan Anak Usia Dini - Mardhiyah, Siti Zumrotul; Muthohar, Sofa (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Instilling moral and religious values from an early age is very important for shaping children's religious character. One effective and enjoyable learning method is through singing religious songs. This study aims to explain the application of the religious singing method in improving the religious knowledge of early childhood students at RA Imama Kedungpane, Mijen, Semarang City. The study employs a qualitative approach with all students in class B2 as subjects. Data collection techniques include observation, interviews, and documentation. The results indicate that the religious singing method creates a pleasant learning environment, facilitates children's understanding of religious material, and enhances their religious knowledge. The religious songs used in the learning activities made the children more enthusiastic and actively involved in the learning process. The study also identified positive responses from the children during the activities and demonstrated the potential of this method as a learning strategy that supports the development of religious values in young children. Therefore, the religious singing method is worthy of further development as part of educational innovation in early childhood education in general.